Hypothalamo-pituitary-adrenal function in intrinsic non-atopic asthma. - Collins, J V (1975)
Sixteen patients with intrinsic non-atopic asthma with persistent wheezing who had never been treated with corticosteroids showed normal adrenocortical responses to prolonged stimulation with Tetracosactin Depot. In a subgroup of six patients the hypothalamo-pituitary-adrenal (HPA) response to a standard insulin stress test was normal. It is concluded that impaired responsiveness of the HPA axis is unlikely to be a common factor in initiating or maintaining airways obstruction in patients with intrinsic asthma.